One year of treatment with elexacaftor/tezacaftor/ivacaftor in patients with cystic fibrosis homozygous for the F508del mutation causes a significant increase in liver biochemical indexes - Castaldo, Alice; Gelzo, Monica; Iacotucci, Paola; Longobardi, Annalisa; Taccetti, Giovanni; Terlizzi, Vito; Carnovale, Vincenzo (Frontiers in Molecular Biosciences, 2024)
Introduction: Modulators of cystic fibrosis transmembrane conductance regulator mutated protein significantly improved the outcome of patients with cystic fibrosis (CF). We describe 63 patients who were independently followed up in two CF regional centers (i.e., Campania and Tuscany regions). Methods: All patients were homozygous for the F508del mutation and were treated with lumacaftor/ivacaftor (LI) for 3 years, followed by 1 year of treatment with elexacaftor/tezacaftor/ivacaftor (ETI). We studied the biochemical parameters of liver damage and cholesterol metabolism. Results: Beyond the improvement of BMI and lung function with LI treatment and even more with ETI, we found that the 3 years of LI treatment significantly improved liver function parameters (total and conjugated bilirubin, ALT, AP, and GGT), while the subsequent ETI treatment caused a significant increase of such parameters. Discussion: We confirm that treatment with LI does not correct hypocholesterolemia, whereas treatment with ETI significantly increases serum cholesterol. Such an increase is likely due to enhanced de novo biosynthesis, as indicated by the significant increase in serum lathosterol, and it is likely that the subsequent liver cholesterol accumulation may contribute to triggering inflammation and worsening liver biochemical indexes. The increase in serum bilirubin and ALT that we observed in approximately 94% and 84% of patients treated with ETI, respectively, suggests further investigation of the impact of ETI therapy on liver function indexes.